2017
DOI: 10.14306/renhyd.21.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in allergy treatment: a literature review

Abstract: Allergy is a exacerbate response of immune system to a triggering element. A probable cause of allergies is gut microbiota composition. It has strong relationship with development of human immune system and this is formed in intrauterine life and early childhood, crucial periods for formation adequate microbiota. In this sense modulation gut microbiota by probiotics could prevent or help in the treatment of allergic diseases such as allergic rhinitis, asthma, atopic dermatitis and food allergy. Studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This hypersensitivity in immune system tolerance mechanisms seems to be modulated by the gut microbiota (90). Dysbiosis has been incriminated for the development of allergies (91).…”
Section: Allergymentioning
confidence: 99%
See 2 more Smart Citations
“…This hypersensitivity in immune system tolerance mechanisms seems to be modulated by the gut microbiota (90). Dysbiosis has been incriminated for the development of allergies (91).…”
Section: Allergymentioning
confidence: 99%
“…Dysbiosis has been incriminated for the development of allergies (91). Probiotics have been successfully used in the treatment of allergic diseases such as allergic rhinitis, asthma, atopic dermatitis and food allergy (90). However, there is still controversy over their use.…”
Section: Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic reactions often occur due to genetic predisposition and environmental factors. Recently, it is confirmed that human bacterial flora, particularly the intestinal microbiota, plays a crucial role in the development of mucosal immune tolerance during the allergy process; the bacteria interact with innate immune cells like macrophages and dendritic cells and contribute to the maturation of the immune organs and differentiation of Th cells (Crovesy et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%